ANALISIS KEPEMIMPINAN DI INSTITUSI SEKOLAH - Siti Rowi (Institut Pemerintahan Dalam Negeri, 2020)
Each school is led by a principal who among others serves as an educationmanager and as a learning leader. Function as an education manager to run education managementin his school, to pursue the success of the development of students through adequate educationalservices. Function as a learning leader to command school personnel to carry out learning tasks. Inaddition to the two leadership functions in the above school, there are still several other principalleadership functions. In this paper will only focus the discussion on leadership functions in theschool as a school manager and as a teaching leader.